2017
DOI: 10.3389/fpls.2017.01154
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Oilseed Crop Sesamum indicum Enters the “Omics” Era

Abstract: Sesame (Sesamum indicum L.) is one of the oldest oilseed crops widely grown in Africa and Asia for its high-quality nutritional seeds. It is well adapted to harsh environments and constitutes an alternative cash crop for smallholders in developing countries. Despite its economic and nutritional importance, sesame is considered as an orphan crop because it has received very little attention from science. As a consequence, it lags behind the other major oil crops as far as genetic improvement is concerned. In re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 108 publications
(192 reference statements)
2
112
0
4
Order By: Relevance
“…Beyond the traditional use of direct consumption, sesame seeds have diverse applications [8]. The potentially beneficial effects of sesame on human health, because of the presence of natural antioxidants such as sesamin, sesamol and sesamolin, have recently prompted renewed interest in this ancient crop [9,10]. While the production of many crops has declined over the last decade in West Africa's Sahel, the traded quantity of sesame has more than doubled in this area, showing growing interest in the crop [11].…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the traditional use of direct consumption, sesame seeds have diverse applications [8]. The potentially beneficial effects of sesame on human health, because of the presence of natural antioxidants such as sesamin, sesamol and sesamolin, have recently prompted renewed interest in this ancient crop [9,10]. While the production of many crops has declined over the last decade in West Africa's Sahel, the traded quantity of sesame has more than doubled in this area, showing growing interest in the crop [11].…”
Section: Open Accessmentioning
confidence: 99%
“…Some other factors, including plant height, length of capsules and axis height of the first capsule, were found to be strongly associated with sesame' grain yield [29,30]. Some candidate genes, QTLs and associated molecular markers for yield-related traits, have been described previously and could contribute to efficiently improve the West African sesame seed yield through molecular breeding [1,10,31,32].…”
Section: What Can Be the Contributions Of Research Programs In West Amentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that drought resistant genotypes maintain better the seed quality under drought stress compared with the sensitive genotypes. Sesame is essentially grown for its high-quality seed [49]. Hence, sesame genotypes with high ability to provide a good seed quality under stress, are highly desirable.…”
Section: Does Drought Resistance Maintain Good Seed Quality In Sesame?mentioning
confidence: 99%
“…Roots have long been proposed as a major avenue of research to improve crop adaptation to water limitations [55]. However, the diversity of root morphology and architecture in sesame has not been examined until now [49]. Therefore, future research may aim at characterizing the diversity of sesame root morphology and architecture as performed in several crops such as pearl millet [56], maize [57], rice [58] and wheat [59].…”
Section: Important Traits For Efficient Screening For Drought Resistamentioning
confidence: 99%